Arsenic Intoxication Presenting as Peripheral Neuropathy (Bangladesh Journal of Neuroscience, 2013)
Chronic Arsenic Toxicity may have varied clinical presentations ranging from non-cancerous manifestations to malignancy of skin and different internal organs. Chronic arsenic exposure results in dermatologic manifestations prior to overt clinical neuropathy. Arsenic neuropathy causes painful paresthesias and, with higher level or continued exposure, length-dependent weakness. We are reporting two cases of chronic arsenic poisoning who presented initially as peripheral sensory motor neuropathy and skin manifestations. Arsenic poisoning was suspected because many of the other family members also developed similar symptoms simultaneously. The hair samples of these patients contained markedly elevated levels of arsenic. Also the water samples from their household and the neighboring households were found to have alarming levels of inorganic arsenic. Provision of arsenic free drinking water halt further deterioration of symptoms and there was significant improvement of their dermatological & neurological conditions. DOI: http://dx.doi.org/10.3329/bjn.v28i2.17184 Bangladesh Journal of Neuroscience 2012; Vol. 28 (2): 128-131